Investigation of Convergence of Iterative Aggregation Methods for Linear Equations in a Banach Space - Kopach, M.; Obshta, A.; Shuvar, B. (Journal of Vasyl Stefanyk Precarpathian National University, 2015)
The sufficient conditions of convergence for a class of multi-parameter iterative aggregation methods are established. These conditions do not contain the requirements of positivity for the operators and aggregating functionals. Moreover, it is not necessary that the corresponding linear continuous operators are compressing